Analisis Dinamika Rotasi Dalam Sisitem Fisik Dan Aplikasinya - Ifolala Natafati Ziliwu; Albert Elisman Zalukhu (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Rotational dynamics in physical systems has become an important area of study in both classical and modern physics, with applications in advanced technologies such as gyroscopes, navigation devices, and vehicle stabilization. This paper presents a literature review on the fundamental principles of rotation, including Newton's laws, angular momentum, and influencing forces, and examines their application in various contemporary technologies. Through an analysis of recent research, this article aims to identify the latest developments and challenges in the application of rotational dynamics.